2022
DOI: 10.1002/clt2.12131
|View full text |Cite
|
Sign up to set email alerts
|

DNA methylation biomarkers in asthma and rhinitis: Are we there yet?

Abstract: The study of epigenetics has improved our understanding of mechanisms underpinning gene‐environment interactions and is providing new insights in the pathophysiology of respiratory allergic diseases. We reviewed the literature on DNA methylation patterns across different tissues in asthma and/or rhinitis and attempted to elucidate differentially methylated loci that could be used to characterize asthma or rhinitis. Although nasal and bronchial epithelia are similar in their histological structure and cellular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 123 publications
0
16
0
Order By: Relevance
“…Big data with similar cohorts are existing, and maybe it is the time to organize and reanalyze all of them in multiparametric models, taking into account all the factors known to be implicated. In our recent review, reporting DNAm results according to tissue specificity, we had identified a small number of differentially methylated loci common in blood and nasal samples that are annotated to specific genes ( ACOT7 , EPX , KCNH2 , SIGLEC8 , TNIK , FOXP1 , ATPAF2 , ZNF8s62 , ADORA3 , ARID3A , IL5RA , METRNL , ZFPM1 ), making them possible candidates for allergic respiratory disease biomarkers [47]. In the present review, combining the information of different tissues and different associated functions that appear to play decisive roles in development/distinguishing of allergic diseases, we can highlight specific genes.…”
Section: Discussionmentioning
confidence: 99%
“…Big data with similar cohorts are existing, and maybe it is the time to organize and reanalyze all of them in multiparametric models, taking into account all the factors known to be implicated. In our recent review, reporting DNAm results according to tissue specificity, we had identified a small number of differentially methylated loci common in blood and nasal samples that are annotated to specific genes ( ACOT7 , EPX , KCNH2 , SIGLEC8 , TNIK , FOXP1 , ATPAF2 , ZNF8s62 , ADORA3 , ARID3A , IL5RA , METRNL , ZFPM1 ), making them possible candidates for allergic respiratory disease biomarkers [47]. In the present review, combining the information of different tissues and different associated functions that appear to play decisive roles in development/distinguishing of allergic diseases, we can highlight specific genes.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, it is also worth highlighting that methylation patterns could be continually changing with ageing, Tanner stage, asthma severity, and the evolution time of asthma [ 36 , 37 ]. For example, ageing is characterised by global hypomethylation and regions of CpG island hypermethylation [ 36 , 37 ]. These modifications in epigenetics might generate lower gene promoter methylation status in older adolescents.…”
Section: Discussionmentioning
confidence: 99%
“…Epigenetic changes may pass down over two generations, as shown by a murine transgenerational asthma model ( Jahreis et al, 2018 ). Scholars have highlighted the significance of epigenetics in the pathogenesis of asthma and other allergic disorders, suggesting a probability of using epidrugs for prevention ( Legaki et al, 2022 ; Potaczek et al, 2022 ). Epigenetic mechanisms may be initiated to dysregulate transcription factors involved in the activities of T lymphocytes and other immune cells, ultimately resulting in asthma and allergic disease ( Liu et al, 2020b ).…”
Section: Introductionmentioning
confidence: 99%